Algeria’s role in facing international economic crises - Bouhebila, Rabah (Journal of Human Sciences, 2023)
Crises have accompanied man since ancient times, and he dealt with them according to his capabilities to limit their effects. Where disasters claimed many human lives in many parts of the world, not even the industrialized European countries were spared. Interest in the science of crisis management has emerged only recently, and economic movements have failed, including the crisis of the explosion of the “Chernobyl reactor” that affected all sectors, the explosion of a volcano in Europe, the emergence of swine and bird flu, so it dispensed with large amounts of its animal wealth and the unwillingness of countries to buy Those products, and the financial stock market crisis in New York, which faced the American capitalist economy on Black Monday on 19/10/1987, in which stock prices collapsed on the Wall Street Stock Exchange in New York, losing $500 billion. Then the crisis moved to the rest of the global stock exchanges such as the London Stock Exchange. and Tokyo. In view of the negative aspects of the oil-exporting countries, their financial revenues decreased, which negatively affected their economic and development projects and their commodity imports, which harmed the exports of the industrialized countries. The Algerian government took measures to protect the economy and stopped the process of opening the capital of public banks and refused to enter into the adventure of sovereign funds to invest abroad.